1962
DOI: 10.4141/cjss62-011
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Accumulation in Annapolis Valley Orchard Soils

Abstract: Use of arsenicals for insect control has resulted in an appreciable accumulation of arsenic in the surface soil of Annapolis Valley apple orchards. Levels of total arsenic in 25 representative orchards ranged from 9.8 to 124.4 p.p.m., whereas the content of comparable samples taken in non-orchard land ranged from a trace to 7.9 p.p.m. In some orchards the arsenic accumulation is of sufficient magnitude to be detrimental to the growth of such arsenic sensitive crops as peas and beans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

1966
1966
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 3 publications
2
10
0
Order By: Relevance
“…In particular, the relatively high water solubility of soil As measured by a number of studies of lead arsenate-contaminated orchard soils suggests that the potential for As uptake into roots and leaf tissues of some crops could be significant. Arsenic uptake from orchard soils is frequently high enough to cause phytotoxicity in sensitive crops (Bishop and Chisholm 1962; Ross and Crowe 1976). Our own studies of As and Pb uptake from orchard soils by leafy green crops showed that there is a wide range of potential for uptake depending on crop species and the part of the plant analyzed (McBride 2013; McBride et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the relatively high water solubility of soil As measured by a number of studies of lead arsenate-contaminated orchard soils suggests that the potential for As uptake into roots and leaf tissues of some crops could be significant. Arsenic uptake from orchard soils is frequently high enough to cause phytotoxicity in sensitive crops (Bishop and Chisholm 1962; Ross and Crowe 1976). Our own studies of As and Pb uptake from orchard soils by leafy green crops showed that there is a wide range of potential for uptake depending on crop species and the part of the plant analyzed (McBride 2013; McBride et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the relatively high water solubility of soil As measured by a number of studies of lead arsenate-contaminated orchard soils suggests that the potential for As uptake into roots and leaf tissues of some crops could be significant. In fact, As uptake is frequently high enough to cause phytotoxicity in sensitive crops [8, 9]. McBride et al [10] found in one greenhouse experiment that uptake of As into leafy green vegetables from severely contaminated orchard soil (containing 220 and 1300 mg/kg of total As and Pb, respectively) was relatively high (near 10 mg kg −1 As on a dry weight or d.w. basis), and substantially greater than that of Pb (about 3 mg kg −1 Pb d.w.), consistent with the much higher water solubility of As compared to Pb measured in the soil.…”
Section: Introductionmentioning
confidence: 99%
“…Arsenic pollution in soil may have toxic effects in vegetation and can adversely affect the animals that feed on that vegetation. Phytotoxicity studies have shown that 7 ppm soluble arsenic causes injury to rice [3] and 9 ppm to peas, beans, and barley [4]. It has also been reported that the toxicity of arsenic may be reduced by applying sulfates of zinc, iron, and aluminum to the soil [5].…”
Section: Introductionmentioning
confidence: 99%